A Modified Emperor Penguin Optimizer Algorithm for Solving Fixed-Charged Transshipment Problem - Eltoukhy, Mohamed Meselhy; Zakaraia, Mohammad (Informatica, 2024)
The Fixed-Charged Transshipment Problem (FCTP) is a significant optimization challenge in logistics and supply chain management. In this paper, we propose a modified Emperor Penguin algorithm specifically designed for solving the FCTP and introduce new benchmarks for evaluating its performance. Computational results, including mean results, standard deviation, and Relative Standard Deviation (RSD), demonstrate the algorithm's effectiveness and robustness in addressing the FCTP. This research contributes to improving supply chain operations and offers valuable insights for efficient logistics management. The modified Emperor penguin optimizer algorithm is tested on 19 test optimization problems. The comparative results are done to confirm the efficiency of the modified emperor penguin optimizer algorithm (EPO) comparing it with the classic EPO algorithm. After adapting the algorithm, the computational results are implemented on 30 generated FCTP problems showing the mean results and robustness measures.